Sensitivity index for conservation priority ranking in the oil spill response: A case study for the coastal and marine species and habitat types in the Baltic Sea - Riikka Venesjärvi; Ari Jolma; Inari Helle (Ecotoxicology and Environmental Safety, 2023)
Numerous anthropogenic stressors, such as habitat alteration and nutrient enrichment, affect coastal and marine ecosystems around the globe. An additional threat to these ecosystems is accidental oil pollution. The proactive planning of efficient oil spill response actions requires a firm understanding of the spatiotemporal distribution of ecological coastal values at stake, and how these values can be protected in case of an oil spill. In this paper, literature and expert knowledge regarding the life history attributes of coastal and marine species were used to build a sensitivity index to assess the differences in the potential of species and habitat types to be safeguarded from oil. The developed index prioritizes sensitive species and habitat types based on 1) their conservation value, 2) the oil-induced loss and recovery potential, and 3) the effectiveness of oil retention booms and protection sheets to safeguard these entities. The final sensitivity index compares the predicted difference in the state of populations and habitat types five years after an oil spill with and without protective actions. The higher the difference, the more worthwhile the management actions are. Hence, compared to other oil spill sensitivity and vulnerability indexes presented in the literature, the developed index considers the usefulness of protective measures explicitly. We apply the developed index to a case study area in the Northern Baltic Sea to demonstrate the approach. It is noteworthy that the developed index is applicable to other areas as well, as the approach is based on the biological attributes of species and habitat types instead of individual occurrences.